Manajemen Pemberdayaan Dan Pengorganisasian Pendidik Dan Tenaga Kependidikan: Penelitian di Madrasah Tsanawiyah Persis Lempong – Garut - Fahri Sahrul Ramadhan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
One of the successes of educational institutions lies in the precision of an educational manager in empowering and placing educators and educational staff according to their competencies. This research aims to obtain comprehensive information about the empowerment and organization of educators and educational staff at Persis Lempong Islamic Junior High School in Garut. This qualitative descriptive research involves data sources such as the School Principal, Educators (Teachers), Educational Staff, and other sources supporting the research. Data collection procedures include observation, in-depth and structured interviews, and documentation. Data analysis is carried out through the processes of reduction, display, and verification. The research results indicate that the empowerment and organization of educators and educational staff are divided into: (a) Management of Educators and Educational Staff at MTs Persis Lempong – Garut, including: 1) Planning of Educators and Educational Staff, 2) Organization of Educators and Educational Staff, 3) Empowerment of Educators and Educational Staff, 4) Evaluation of Educators and Educational Staff. And (b) Empowerment or Development Programs for Educators and Educational Staff at MTs Persis Lempong – Garut.